Post-discharge formula feeding in preterm infants: A systematic review mapping evidence about the role of macronutrient enrichment. Issue 4 (August 2016) - Teller, Inga C.; Embleton, Nicholas D.; Griffin, Ian J.; van Elburg, Ruurd M.
Summary: Background & aims: Preterm infants are a heterogeneous group and many accumulate growth deficits before and after initial hospital discharge. Although this is associated with worse cognitive outcome, recent meta-analyses suggest that nutrient fortification of breast milk, or the use of nutrient and energy rich formulae after discharge exert little effect on growth and neurodevelopment. However, the complexity of study design, inclusion criteria and outcome parameters, combined with differences in formula composition mean that meta-analysis may overlook important effects of differing interventions in sub-groups. Methods: We systematically identified evidence and mapped the information on Participants, Intervention, Comparator, and Outcome (PICO) from 31 published studies illustrating the marked heterogeneity in study design and interventions next to outcomes on (quality of) growth and neurodevelopment. Results: Despite significant heterogeneity in study design, we found that nutrient enriched diets after discharge show no negative effects but frequently improve growth parameters at some point in the course of the study, in particular for boys. The data indicates that when energy requirements are adequate, increased protein results in increased growth and lean mass (LM) accretion; In particular, higher protein to energy ratios lead to increased lean mass accretion, and increased head circumference (HC) at one year. However, improvements in neurodevelopmental outcome were rarely seen. Conclusion: This comprehensive evidence mapping approach to the field provides a broad but detailed overview of the currently available evidence. Furthermore, we identified key gaps in existing knowledge on the role of nutrient enrichment in the post-discharge period.